The Architectural Layout and Degree of Preservation of the Sanctuary of Pachacamac Archaeological Complex (2nd to 16th Centuries AD, Peru) from the Morphometric Analysis of Orthophotogrammetric Data - Luigi Magnini; Pierdomenico Del Gaudio; Maria Ilaria Pannaccione Apa; Denise Pozzi-Escot; Janet Oshiro; Rommel Angeles; Guido Ventura (Remote Sensing)
Archaeological complexes are characterized by different degrees of damage related to both natural events and anthropogenic triggers. The damage may be assessed through direct observation or remotely acquired data. Here, we present a morphometric analysis of a digital surface model (DSM) obtained from an orthophotogrammetric survey at the Sanctuary of Pachacamac Archaeological Complex, Peru (2nd to 16th centuries AD), which includes temples, enclosures, huacas, and roads. We determine different morphometric parameters to quantitatively describe the architectural layout of the site. These are aspect, slope, range, and topographic position index (TPI). We applied a modified TPI classification to measure the different degrees of preservation of the walls of the archaeological structures and recognize preserved, partly preserved, partly destroyed, and destroyed walls. The walls of the site show different degrees of preservation related to the damage associated with earthquakes and El Niño destructive events. The architectural layout of the archaeological site is defined by NW-SE and NE-SW striking walls. This is due to buildings constructed along the two main NW-SE and NE-SW striking roads of the Qhapac–Ñan road network. The prevailing El Niño wind direction may also explain the observed architectural layout. Morphometric parameters can be used to estimate the degree of conservation of archaeological sites. Our analytical approach can be applied to modern buildings damaged by natural events or human activities.